Synthesis, Characterization and Biological Activities of Novel a 1,2,3,4-tetrahydroquinazoline and Its Nickel(II) Complexes - Çolak, Alper; Taş, Murat; İrez, Gazi; Büyükgüngör, Orhan; Çolak, Ferdağ; Günay, Handan (Gebze Teknik Üniversitesi, 2017)
The 2-methyl-2-(1-hydroxyiminoethyl)-1,2,3,4-tetrahydroquinazoline (HL or 1) and its novel Ni(II) complexes, square-planar [Ni(L)(LH)]·(NO3) (2) and octahedral [NiCl2(LH)(H2O)2]·(H2O) (3), have been synthesized. The ligand and complexes have been characterized by means of elemental, IR, UV-Vis. spectroscopic studies, 1H-NMR, 13C-NMR, magnetic susceptibility, thermal analysis, mass spectroscopy and X-ray diffraction technique. The HL ligand crystallizes in the P21/c. Antimicrobial activity of ligand (1) and complexes (2 and 3) was evaluated by the agar diffusion method. Complex 2 showed weak antimicrobial activity against tested microorganism strains. Complex 3 exhibited moderate antimicrobial activity against Staphylococcus epidermidis and Candida albicans.
Keywords: Chemical Engineering; Kimya Mühendisliği